Beast from the East: The Griffin’s Journey to Dalmatian Eleventh-Century Sculpture - Skoblar, Magdalena (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
This article argues that the introduction of griffins in Dalmatian eleventh-century sculpture was sparked by the increased exposure of the region’s main ports to Byzantine and/or Islamic silks, which frequently featured these mythical creatures. This exchange was driven by Venetian merchants who benefitted from the trading privileges granted to Venice by Byzantine emperors in the tenth and the eleventh centuries. The documented routes of two individuals, travelling from Zadar to Constantinople and from Split to Antioch respectively, point to potential direct purchases from these two centres of silk production and trade. The article concludes with an examination of the griffin’s symbolic significance in the carvings under discussion.